2018
DOI: 10.1021/acs.cgd.8b01339
|View full text |Cite
|
Sign up to set email alerts
|

Protein Crystallization Irradiated by Audible Sound: The Effect of Varying Sound Frequency

Abstract: Protein crystallization is a process that is very sensitive to the physical environment. Audible sound is an environmental characteristic that can significantly affect the crystallization process. Previously, it was found that the crystallization result is frequency dependent, that is, the crystallization of protein under different sound frequencies yields different results. Here, we further investigate the effect of varying frequency (or a frequency program) on protein crystallization. Twelve different freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The change in temperature might be a result of absorbed heat generated by the sound perturbation. Previous works have shown that at least part of the audible sound energy is transformed into heat that can be absorbed by water, and spent on the reorganization of water molecular structure, causing the change in its temperature [ 6 , 10 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The change in temperature might be a result of absorbed heat generated by the sound perturbation. Previous works have shown that at least part of the audible sound energy is transformed into heat that can be absorbed by water, and spent on the reorganization of water molecular structure, causing the change in its temperature [ 6 , 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our findings, even though based on investigation of sound effects on the simplest aqueous systems and only two frequencies, may prove to have wider implications, especially considering the major role water plays as a matrix for biological systems. Recent scientific reports showed that audible sound promotes crystallization of proteins, which is frequency-dependent, and shows some variation based on protein type; this was found to be connected with the change of temperature and evaporation of protein solution [ 6 , 10 ]. Although the mentioned studies were performed using different frequencies and even variable-frequency sound perturbation, there is a common link with our study—sound affects water-based systems and changes their molecular structure in a frequency- and sample-type-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations